Competitive intelligence failures: An information behaviour lens to key intelligence and information needs. Issue 4 (16th July 2018) - Maungwa, Tumelo; Fourie, Ina
Abstract : Purpose: Competitive intelligence failures have devastating effects in marketplaces. They are attributed to various factors but seldom explicitly to information behaviour. This paper addresses causes of competitive intelligence failures from an information behaviour lens focussing on problems with key intelligence and information needs. The exploratory study was conducted in 2016/2017. Managers (end-users) identify key intelligence needs on which information is needed, and often other staff members seek the information (proxy information seeking). The purpose of this paper is to analyse problems related to key intelligence and information needs, and make recommendations to address the problems. Design/methodology/approach: The study is placed in a post-positivism research paradigm, using qualitative and limited quantitative research approaches. In total, 15 participants (competitive intelligence professionals and educators/trainers originating from South Africa and the USA) contributed rich data through in-depth individual interviews. Findings: Problems associated with articulation of information needs (key intelligence needs is the competitive intelligence term – with a broader scope) include inadequate communication between the person in need of information and the proxy information searcher; awareness and recognition of information needs; difficulty in articulation, incomplete and partial sharing of details of needs. Research limitations/implications: Participant recruitment was difficult, representing mostly from South Africa. The findings from this exploratory study can, however, direct further studies with a very understudied group. Practical implications: However, revealed valuable findings that can guide research. Originality/value: Little has been published on competitive intelligence from an information behaviour perspective. Frameworks guiding the study (a combination of Leckie et al. 's 1996 and Wilson's, 1981 models and a competitive intelligence life cycle), however, revealed valuable findings that can guide research.